2016
DOI: 10.1111/cea.12710
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implication of genetic variants of IL13 and STAT4 in airway remodelling with bronchial asthma

Abstract: SummaryBackground Several gene variants identified in bronchial asthmatic patients are associated with a decrease in pulmonary function. The effects of this intervention on pulmonary function have not been fully researched. Objective We determined the effects of high-dose inhaled corticosteroids (ICSs) on decreased pulmonary function in asthmatic Japanese patients with variants of IL13 and STAT4 during long-term treatments with low to mild doses of ICS. Methods In this study, 411 patients with bronchial asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Low‐molecular‐mass HA (LMMHA), a product of rapid turnover and degradation of HA, can serve as an intracellular signalling molecule in inflammation and has been found to be pro‐inflammatory . LMMHA is dramatically increased in patients with idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, asthma and acute respiratory distress syndrome . A previous study on the role of LMMHA in lung injury revealed that blocking the effect of LMMHA with specific peptides decreases neutrophil infiltration and fibrosis activity and alleviates lung tissue damage in a bleomycin‐mediated LMMHA‐induced mouse lung injury model .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low‐molecular‐mass HA (LMMHA), a product of rapid turnover and degradation of HA, can serve as an intracellular signalling molecule in inflammation and has been found to be pro‐inflammatory . LMMHA is dramatically increased in patients with idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, asthma and acute respiratory distress syndrome . A previous study on the role of LMMHA in lung injury revealed that blocking the effect of LMMHA with specific peptides decreases neutrophil infiltration and fibrosis activity and alleviates lung tissue damage in a bleomycin‐mediated LMMHA‐induced mouse lung injury model .…”
Section: Introductionmentioning
confidence: 99%
“…3 LMMHA is dramatically increased in patients with idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, asthma and acute respiratory distress Abbreviations: BALF, bronchoalveolar lavage fluid; ECM, extracellular matrix; ERK 1/2, extracellular signal-regulated kinase 1/2; IFN-b, interferon-b; IL-1b, interleukin-1b; IRF-3, interferon regulatory factor 3; KC, keratinocyte cell-derived chemokine; LMMHA, low-molecular-mass hyaluronan; Mcl-1, myeloid leukaemia cell differentiation protein; MMP-9, matrix metalloproteinase-9; MPO, myeloperoxidase; PBS, phosphate-buffered saline; PI3K, phosphoinositide 3-kinase; TLR, Toll-like receptor; WT, wild-type ª 2018 John Wiley & Sons Ltd, Immunology, 155, 387-395 syndrome. [4][5][6][7] A previous study on the role of LMMHA in lung injury revealed that blocking the effect of LMMHA with specific peptides decreases neutrophil infiltration and fibrosis activity and alleviates lung tissue damage in a bleomycin-mediated LMMHA-induced mouse lung injury model. 8 These studies establish the importance of LMMHA in respiratory disorders and encourage further study of the pro-inflammatory properties of LMMHA.…”
Section: Introductionmentioning
confidence: 99%
“…Another study failed to find statistical significance between rs20541 polymorphism and treatment and symptom severity of asthma [14]. Another group also reports an association between the IL13 AA rs20541 genotype and airway remodeling in Japanese asthmatics [15]. …”
Section: Introductionmentioning
confidence: 99%
“…9 In northern European populations of asthmatic children and young adults, GLCCI1 genotype rs37972 has been demonstrated to not be associated with an ICS efficacy decrease in lung function and asthma symptom scores. 11,12 Thus, increased FEV1 or recovered airway remodeling were dependent on the genetic background and treatment content. Administration of high-dose ICS to asthmatic patients with genetic variants of STAT4 did not respond to it, whereas the genetic variants of IL13 AA might avoid the advancing of airway remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of high-dose ICS to asthmatic patients with genetic variants of STAT4 did not respond to it, whereas the genetic variants of IL13 AA might avoid the advancing of airway remodeling. 11,12 Thus, increased FEV1 or recovered airway remodeling were dependent on the genetic background and treatment content. In the current study, we aimed to assess whether variants in the GLCCI1 rs37972 and rs37973 genotypes were associated with relationships between lung function and treatment in Japanese adults receiving ICS treatment, and to identify GLCCI1 positive cells in the bronchial airways.…”
Section: Introductionmentioning
confidence: 99%